2014
DOI: 10.3109/1547691x.2014.904025
|View full text |Cite
|
Sign up to set email alerts
|

Potential preventive role of lactic acid bacteria against Aflatoxin M1immunotoxicity and genotoxicity in mice

Abstract: Aflatoxin M 1 (AFM 1 ) is a mycotoxin produced by numerous Aspergillus species in pre-or postharvest cereals and milk. Exposure to AFM 1 imparts potent economic losses in the livestock industry. Toxicologically, it also causes severe immune system problems. The aims of this study were to evaluate a new AFM 1 -binding/degrading microorganism for biologic detoxification, to examine its ability to degrade AFM 1 in liquid medium, and to evaluate its potential for in vivo preventative effects against AFM 1 -induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 52 publications
0
9
0
2
Order By: Relevance
“…18,19 Exposure of mice to 100 g of AFM 1 kg −1 resulted in significantly lower gains in body mass (BM), greater numbers of total white blood cells (WBCs) in blood, and altered absolute and relative numbers of types of cells in thymus and spleen. 20 Exposure of Balb/c mice to AFM 1 negatively affected several parameters in the immune system, including total numbers of CD 3+ , CD 54+ , CD 4+ and CD 56+ cells and indices of lymphoid organs. 21 The present study aimed to investigate the toxicity of AFM 1 on different aspects of immune systems (innate and adaptive immune responses) after repeated intraperitoneal (IP) administration for 28 days.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…18,19 Exposure of mice to 100 g of AFM 1 kg −1 resulted in significantly lower gains in body mass (BM), greater numbers of total white blood cells (WBCs) in blood, and altered absolute and relative numbers of types of cells in thymus and spleen. 20 Exposure of Balb/c mice to AFM 1 negatively affected several parameters in the immune system, including total numbers of CD 3+ , CD 54+ , CD 4+ and CD 56+ cells and indices of lymphoid organs. 21 The present study aimed to investigate the toxicity of AFM 1 on different aspects of immune systems (innate and adaptive immune responses) after repeated intraperitoneal (IP) administration for 28 days.…”
Section: Introductionmentioning
confidence: 98%
“…Another study indicated that exposure to a combination of AFM 1 and AFM 2 significantly reduced the release of nitric oxide by lipopolysaccaride (LPS)‐induced macrophages in a concentration‐dependent manner . Exposure of mice to 100 μg of AFM 1 kg −1 resulted in significantly lower gains in body mass (BM), greater numbers of total white blood cells (WBCs) in blood, and altered absolute and relative numbers of types of cells in thymus and spleen . Exposure of Balb/c mice to AFM 1 negatively affected several parameters in the immune system, including total numbers of CD 3+ , CD 54+ , CD 4+ and CD 56+ cells and indices of lymphoid organs .…”
Section: Introductionmentioning
confidence: 99%
“…Ochratoxin, particularly OTA is considered as a potent carcinogen and classified in Group 2B by the International Agency for Research on Cancer (IARC, 1993) for humans. Ochratoxins are considered to be the main reason for causing a serious anomaly namely Balkan Endemic Nephropathy (BEN) in humans exposed to its dietary exposure (Zahoor-ul-Hassan et al, 2012;Solcan et al, 2015;Iftikhar et al, 2015;Ben Salah-Abbes et al, 2015). Ochratoxin A (OTA) causes adverse effects in poultry and is considered to be the most toxic mycotoxin along with aflatoxins for poultry birds.…”
Section: Introductionmentioning
confidence: 99%
“…A inibição do crescimento de micro-organismos produtores de AFLAs, bem como o efeito do uso de BAL tem sido avaliados em estudos in vivo (ABBÈS et al, 2016;CHEN et al, 2019;GOMAA;ABDELALL;EL-MAHDY, 2018;GUIMARÃES et al, 2018;JEBALI et al, 2018;NATEGHI et al, 2016;NDUTI et al, 2016;ONILUDE et al, 2005;SALAH-ABBÈS et al, 2015) Lactobacillus acidophilus La-5 B 1 (3, 25 a 6,0 µg L -1 ) e M 1 (1,0 a 2,0 µg L -1 ) / Leite A maior redução de AFLAB 1 foi utilizando a BAL, βglucana e polidextrose atingindo 35,5%, e a redução de AFLAM 1 foi de 71,5%. A melhor condição experimental foi 6,5 µg L -1 de AFLAB 1 e 2,0 µg L -1 de AFLAM 1 com tempo de incubação de 0 h e adição de probióticos e inulina (0,75%).…”
Section: Bactérias áCido Láticasunclassified